Stereo‐ and Regioselective Cu‐Catalyzed Hydroboration of Alkynyl Chalcogenoethers. Issue 13 (25th May 2020) - de Oliveira, Isadora M.; Esteves, Henrique A.; Darbem, Mariana P.; Sartorelli, Arthur; Correra, Thiago C.; Rodrigues‐Oliveira, André F.; Pimenta, Daniel C.; Zukerman‐Schpector, Julio; Manarin, Flávia; Stefani, Hélio A.
Abstract: A mild stereo‐ and regioselective Cu‐catalyzed hydroboration method for the synthesis of (Z)‐seleno‐alkenyl boronates and (Z)‐thio‐alkenylboronates from internal alkynes in the presence of commercially available B2 pin2 is presented. This highly selective transformation relies on the use of N‐heterocyclic carbene (NHC) complex IPrCuCl as the active catalytic species. We also explore the functionalization of the alkenylboronates obtained via oxidation to give α ‐chalcogeno ketones, useful building blocks for the synthesis of more complex chalcogen‐containing molecules. Abstract : Selective hydroboration : A mild stereo‐ and regioselective Cu‐catalyzed hydroboration method for the synthesis of (Z)‐seleno‐alkenyl boronates and (Z)‐thio‐alkenylboronates from internal alkynes in the presence of commercially available B2 pin2 is presented. This highly selective transformation relies on the use of N‐heterocyclic carbene (NHC) complex IPrCuCl as the active catalytic species. We also explore the functionalization of the alkenylboronates obtained via oxidation to give α ‐chalcogeno ketones, useful building blocks for the synthesis of more complex chalcogen‐containing molecules.